2006
DOI: 10.1037/0278-6133.25.2.198
|View full text |Cite
|
Sign up to set email alerts
|

The role of depression symptoms in dialysis withdrawal.

Abstract: Among end-stage renal disease (ESRD) patients on hemodialysis, death from withdrawal from life-sustaining dialysis is increasingly common. The present study's objective was to examine depression as a potential risk factor for hemodialysis withdrawal. Two hundred forty ESRD hemodialysis (133 male and 107 female) patients were followed for an average of 4 years after depression symptom assessment. Of these, 18% withdrew from dialysis. Using multivariate survival analysis and after controlling for the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 39 publications
0
66
1
3
Order By: Relevance
“…4 In the ongoing Following Rehabilitation, Economics, and Everyday Dialysis Outcome Measurements study, daily hemodialysis patients had fewer depressive symptoms, better sleep quality, and shorter postdialysis recovery time. 24,25 Depression severity has been identified as a predictor of dialysis withdrawal 26 ; risk of death from dialysis withdrawal was markedly lower in DHHD patients in this study. In addition, frequent hemodialysis typically reduces intensity of pharmacological treatment, with decreased use of antihypertensive agents and phosphate binders.…”
Section: Discussionmentioning
confidence: 81%
“…4 In the ongoing Following Rehabilitation, Economics, and Everyday Dialysis Outcome Measurements study, daily hemodialysis patients had fewer depressive symptoms, better sleep quality, and shorter postdialysis recovery time. 24,25 Depression severity has been identified as a predictor of dialysis withdrawal 26 ; risk of death from dialysis withdrawal was markedly lower in DHHD patients in this study. In addition, frequent hemodialysis typically reduces intensity of pharmacological treatment, with decreased use of antihypertensive agents and phosphate binders.…”
Section: Discussionmentioning
confidence: 81%
“…101 However, true suicidal behavior and ideation might be more difficult to differentiate in this population. 24,34,103,105 The early findings might have been a result of evaluating white populations at high risk in an era of relatively primitive dialytic delivery techniques. More recent studies show suicide to be less prevalent in contemporary ESRD populations, 24,99 although the rate is 84% higher than in the general population.…”
Section: Withdrawal From Dialysismentioning
confidence: 99%
“…24,100,101 A recent study found that depression was a predictor of the decision to withdraw from dialysis. 105 Despite the high rate of withdrawal from dialysis, the extent to which it should be considered a suicide equivalent is unclear and controversial. 24,102,104 It is known that ESRD patients have the potential to commit suicide with relative ease through noncompliance, and, in fact, an early study reported rates of suicide to be 100 to 400 times higher in dialysis patients compared with the general population.…”
Section: Withdrawal From Dialysismentioning
confidence: 99%
“…McDade-Montz et al (46) studied the role of depression in dialysis withdrawal. A one-point increase in the total BDI score was associated with a 5.2% increase in the risk for withdrawing from dialysis in a predominately white population (46). Recently, Kurella et al (47) sought to determine the incidence of suicide among patients with ESRD nationwide.…”
Section: Diagnosismentioning
confidence: 99%